Cyclic sulfur metabolites from Allium schoenoprasum var. foliosum. (February 2019) - Fukaya, Masashi; Nakamura, Seikou; Kyoku, Yoshika; Nakashima, Souichi; Yoneda, Taichi; Matsuda, Hisashi
Graphical abstract: Allium schoenoprasum var. foliosum . Highlights: Three new cyclic sulfur-containing compounds, folionins A1, A2 and B, were isolated from Allium schoenoprasum var. foliosum . These compounds were extracted with acetone. The hypothetical biosynthetic pathways of folionins were suggested. Abstract: Three sulfur-containing cyclic compounds, folionins A1 (1 ), A2 (2 ), and B (3 ), were isolated from acetone extract of the whole plant of Allium schoenoprasum var. foliosum . Their chemical structures were determined by physicochemical methods. The compounds possess a 3, 4-dimethyltetrahydrothiophene moiety in common and a methyl disulfide or a propyl disulfide as side chain. This study aimed to determine the relative configurations of the new compounds.